Indikator Biokimia untuk Identifikasi Anemia Defisiensi Besi di Indonesia: Tinjauan Literatur: Indikator Biokimia untuk Identifikasi Anemia Defisiensi Zat Besi di Indonesia - Helmyati, Siti; Hasanah, Fina Cahya; Putri, Febriani; Sundjaya, Tonny; Dilantika, Charisma (Universitas Airlangga, 2023)
Background: The World Health Organization (WHO) states that adolescents are at risk of developing anemia. The initial step in identifying iron deficiency anemia (IDA) is through screening. In addition, the WHO framework aims to accelerate the reduction of anemia worldwide by achieving specific goals, including an increase in anemia screening. Objectives: This study aims to determine the use of biochemical indicators in screening for the identification of IDA status in Indonesia. Methods: Literature searches were conducted in the PubMed, Scopus, ScienceDirect, and Garuda databases following the PRISMA guidelines. Articles from journals indexed in Scopus Q1 to Q4 or Sinta 1 to Sinta 3 with an experimental or observational research design in Indonesia were reviewed. Discussion: Anemia screening was performed to determine IDA status, which was measured by the following parameters: hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC). Hb is an indicator of IDA in populations with a high prevalence of IDA. MCV is calculated by dividing hematocrit by red blood cell count. MCH refers to the average absolute hemoglobin content of the red blood cells, while MCHC refers to the concentration of hemoglobin in the red blood cells. Serum ferritin (SF) is a highly reliable and sensitive indicator for assessing iron stores and clinical status in the field. In addition, serum transferrin receptor (STfR) is a more stable indicator than serum transferrin (ST). SF can differentiate between IDA caused by anemia or chronic diseases. Conclusions: Combining hemoglobin and SF improves sensitivity and specificity in detecting the severity of IDA. STfR can also be used as an indicator for IDA. The use of the STfR and SF indicators is the best biochemical approach to IDA.